Podstawy zaskarżenia skargi z art. 7 § 1 Kodeksu karnego wykonawczego na decyzje organów wykonujących orzeczenia (zagadnienia wybrane) - Tarapata, Szymon (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
The text refers to the grounds for complaint under Article 7 § 1 of the Executive Criminal Code (k.k.w.) against decisions of authorities executing judgments in criminal cases. Article 7 § 1 k.k.w. indicates that such a decision can be challenged because of its contrariety to law. This expression has a very broad meaning. Therefore, it is possible to contest the findings on which the decision is based, as well as the disparity of the penalty imposed on the convicted.